Effect of health system on the association of rurality and level of disadvantage with receipt of diabetic eye screening. Issue 6 (14th December 2022) - Lock, Loren J; Channa, Roomasa; Brennan, Meghan B; Cao, Ying; Liu, Yao
Abstract : Introduction: Rural versus urban disparities have been observed in diabetic eye screening, but whether the level of disadvantage in rural versus urban areas is related to these disparities is unclear. Our goal was to determine the role of level of disadvantage in explaining the effect of health systems on rural and urban disparities in diabetic eye screening. Research design and methods: This is a retrospective cohort study using an all-payer, state-wide claims database covering over 75% of Wisconsin residents. We included adults with diabetes (18–75 years old) who had claims billed throughout the baseline (2012–2013) and measurement (2013–2014) years. We performed multivariable regressions to assess factors associated with receipt of diabetic eye screening. The primary exposure was the primary care clinic's combined level of rurality and disadvantage. We adjusted for the health system as well as patient-level variables related to demographics and comorbidities. Health system was defined as an associated group of physicians and/or clinics. Results: A total of 118 707 adults with diabetes from 698 primary care clinics in 143 health systems met the inclusion criteria. Patients from urban underserved clinics were less likely to receive screening than those from rural underserved clinics before adjusting for health system in the model. After adjusting for health system fixed effects, however, the directionality of the relationship between clinic rurality and screening reversed: patients from urban underserved clinics were more likely to receive screening than those from rural underserved clinics. Similar findings were observed for both Medicare and non-Medicare subgroups. Conclusions: The effect of health system on receipt of diabetic eye screening in rural versus urban areas is most pronounced in underserved areas. Health systems, particularly those providing care to urban underserved populations, have an opportunity to increase screening rates by leveraging health system-level interventions to support patients in overcoming barriers from social determinants of health.